Modelling, simulations and operational performance of a stand-alone hybrid wind/PV energy system supplying induction motor for pumping applications. (2018) - Abuashour, Mohammed I.; Widyan, Mohammad S.; Sweidan, Tha'er O.; Momani, Mohammed A.
This paper presents a stand-alone Wind/PV hybrid power system supplying a three phase induction motor for pumping applications. The nonlinear dynamical mathematical model for the system components is presented and used for numerical simulations. The system comprises a fixed speed wind turbine driving a self-excited induction generator (SEIG) terminated by capacitor bank, and a photovoltaic (PV) array integrated via DC-DC converter, inverter and LC filter. The two sources feed (IM) driving a centrifugal pump. The duty ratio of the converter is controlled to maintain constant voltage at common coupling point. System performance is tested by changing the load torque coupled to the motor at certain solar irradiance levels and with fixing load torque with successive step changes of the solar irradiance levels. It is concluded that the system has the ability to run at wide range of solar intensity levels and motor loading conditions. Numerical simulations are executed using MATLAB software.